Tantangan PAI Menghadapi Globalisasi Dalam Meningkatkan Karakter Siswa Di Bandar Lampung - Rohili, Tahir (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This research explores the challenges faced by Islamic Religious Education (PAI) in responding to the impact of globalization on the character development of students in Bandar Lampung. Utilizing a qualitative literature review method, the study identifies the key issues including value disorientation among students, the normative rigidity of PAI curriculum, and limited pedagogical adaptability by educators. The findings indicate that globalization has not only introduced external pressures such as media influence and cultural shifts, but also exposed internal weaknesses in the implementation of PAI. Despite these challenges, the study also reveals opportunities for transformation through the integration of digital Islamic media, development of contextualized teaching approaches, and strengthened collaboration among schools, families, and communities. These strategies are essential for PAI to maintain its relevance and effectiveness in nurturing a generation that is religiously committed and globally competent. The study underscores the urgency for systemic reform in curriculum design, teacher competence, and learning innovation in order to revitalize Islamic education in the era of globalization.